EFISIENSI KINERJA RANTAI PASOK IKAN PATIN DI KABUPATEN PRINGSEWU - clara yolandika; Dayang Berliana; Nuni Anggraini (Journal of Food System & Agribusiness, 2021)
This study aims to analyze the efficiency of the supply chain performance of pangasius in Pringsewu. This research was conducted in Pringsewu, Lampung. The types of data used in this study were primary data and secondary data. Respondents in this study were partner farmers who produced pangasiush as many as 43 partner farmers. Measurement of supply chain performance was carried out using the Data Envelopment Analysis (DEA) method. The result of this research was that the performance of the supply chain of pangasius in Pringsewu was mostly technically efficient, there were only 7 partner farmers who were still not technically efficient. This inefficient performance of pangasius farmers was due to the presence of slack input (excess input). Efforts that can be made to improve supply chain performance efficiency can reduce order fulfillment lead times by 18.42%, order fulfillment cycles by 12.50%, supply chain costs 28.51%, and supply chain flexibility by 15%.